Chemical composition and ruminal digestion of corn silage with Morus alba L. foliage - Jimenéz-Guillén, Regulo; Noriega Cantú, David Heriberto; Rojas-Hernández, Saúl; Olivares Pérez, Jaime; Villa-Mancera, Abel; Olmedo-Juárez, Agustín; Paredes-Díaz, David; Hernández-Hernández, Humberto (Ecosistemas y Recursos Agropecuarios, 2019)
Chemical composition and ruminal digestion parameters were mea- sured in the silage of the whole corn plant (Zea mays L.) mixed with mulberry foliage (Morus alba L.) in ratio of 100:0, 80:20, 60:40, 40:60, 20:80 and 00:100% of fresh forage weight, respectively. The 40:60 ratio of corn: mulberry increased crude protein content (CP = 14.28%) and decreased hemicellulose (12.15%), neutral (NDF = 28.00%) and acidic (ADF = 15.85%) detergent fiber, compared to 100: 0% ratio, respectively, which led to a 21.3% increase in in vitro dry matter digestibility (IVDMD). Also ammoniacal nitrogen 7.40% (NH3-N/total N) was higher in the ratio 40:60%, with pH of 4.19 which is normal for silages, which translates the buffer activity correct of ammonia and its importance for silage fermentation stability. The correlation (r = 0.61, p < 0.001) indicated that at higher CP content, higher is IVDMD and hemicellulose (r = -0.99), ADF (r = -0.98) and NDF (r = -0.98) indicated that these fibrous compounds decreased IVDMD (p < 0.001). The regression showed that the increase in content CP (0.555%, p < 0.01) and IVDMD (0.3391%, p < 0.001) with the decrease of NDF (-0.3526%), ADF (-0.1623%) and hemicellulose (-0.1903%) (p < 0.001) in mixed mini silos, was attributed to mulberry foliage addition. It is concluded that the contribution of dry matter and nitrogen of mulberry, decreased the fiber content and increased digestibility parameters of silage when it is elaborated in ratio of 40:60 corn and mulberry, respectively.